Application of Prostate Cancer Models for Preclinical Study: Advantages and Limitations of Cell Lines, Patient-Derived Xenografts, and Three-Dimensional Culture of Patient-Derived Cells - Namekawa, Takeshi; Ikeda, Kazuhiro; Horie-Inoue, Kuniko; Inoue, Satoshi (Cells (Basel, Switzerland), 2019)
Various preclinical models have been developed to clarify the pathophysiology of prostate cancer (PCa). Traditional PCa cell lines from clinical metastatic lesions, as exemplified by DU-145, PC-3, and LNCaP cells, are useful tools to define mechanisms underlying tumorigenesis and drug resistance. Cell line-based experiments, however, have limitations for preclinical studies because those cells are basically adapted to 2-dimensional monolayer culture conditions, in which the majority of primary PCa cells cannot survive. Recent tissue engineering enables generation of PCa patient-derived xenografts (PDXs) from both primary and metastatic lesions. Compared with fresh PCa tissue transplantation in athymic mice, co-injection of PCa tissues with extracellular matrix in highly immunodeficient mice has remarkably improved the success rate of PDX generation. PDX models have advantages to appropriately recapitulate the molecular diversity, cellular heterogeneity, and histology of original patient tumors. In contrast to PDX models, patient-derived organoid and spheroid PCa models in 3-dimensional culture are more feasible tools for in vitro studies for retaining the characteristics of patient tumors. In this article, we review PCa preclinical model cell lines and their sublines, PDXs, and patient-derived organoid and spheroid models. These PCa models will be applied to the development of new strategies for cancer precision medicine.